2021
DOI: 10.1016/j.patter.2021.100374
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the dots: The boons and banes of network modeling

Abstract: Summary Network modeling transforms data into a structure of nodes and edges such that edges represent relationships between pairs of objects, then extracts clusters of densely connected nodes in order to capture high-dimensional relationships hidden in the data. This efficient and flexible strategy holds potential for unveiling complex patterns concealed within massive datasets, but standard implementations overlook several key issues that can undermine research efforts. These issues range from dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Biological studies are increasingly pursuing and obtaining data on larger scales and at multiple levels in the molecular hierarchy of the study system. One approach for dealing with the multiplicity of data in modern biology is to represent the relationships in the data as a network [1]. Each entity in a dataset (e.g., each gene) becomes a node, and an edge between two nodes represents a relationship that has been measured or predicted between those nodes (e.g., their co-expression in a population, sharing of common protein domains, similarity of methylation state, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Biological studies are increasingly pursuing and obtaining data on larger scales and at multiple levels in the molecular hierarchy of the study system. One approach for dealing with the multiplicity of data in modern biology is to represent the relationships in the data as a network [1]. Each entity in a dataset (e.g., each gene) becomes a node, and an edge between two nodes represents a relationship that has been measured or predicted between those nodes (e.g., their co-expression in a population, sharing of common protein domains, similarity of methylation state, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the use of standard correlation metrics in network modeling leads to increased type II errors in the presence of subtype groups 5,7,9,11 . All the correlation measures that we have examined, including Pearson’s correlation coefficient 12 , r -squared 13 , dot product 14 , and mutual information 15 , return single scalar values that are crippled by heterogeneity 5 . They are universal measures, in that individuals in the entire group are viewed as a whole and thus subtle but crucial subgroup structures, which manifest heterogeneity of the individuals in the group, are ignored.…”
Section: Introductionmentioning
confidence: 99%
“…They are universal measures, in that individuals in the entire group are viewed as a whole and thus subtle but crucial subgroup structures, which manifest heterogeneity of the individuals in the group, are ignored. If two analytes are highly correlated for a subset of individuals but not at all correlated for the others, the correlation value is reduced due to the latter individuals, thereby contributing to false negative signals 5,11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations